Pricing Parisian Option under a Stochastic Volatility Model - Min-Ku Lee; Kyu-Hwan Jang (Journal of Applied Mathematics)
We study the pricing of a Parisian option under a stochastic volatility model. Based on the manipulation problem that barrier options might create near barriers, the Parisian option has been designed as an extended barrier option. A stochastic volatility correction to the Black-Scholes price of the Parisian option is obtained in a partial differential equation form and the solution is characterized numerically.